Current status of and future strategies for multimodality treatment of unresectable stage III nonsmall cell lung cancer - Huber, Rudolf M.; Reck, Martin; Thomas, Michael (The European respiratory journal, 2013)
Stage III nonsmall cell lung cancer (NSCLC) encompasses a heterogeneous group of patients, some of whom may be candidates for potentially curative surgery, although for the majority surgery is not an option. Recommended therapy for patients with unresectable stage III disease is concurrent treatment with chemotherapy and thoracic radiotherapy, although even with this dual modality therapy survival remains disappointing. Novel classes of agents including targeted therapies have been shown to improve survival in advanced stage NSCLC, raising the possibility that these agents may have benefits in multimodal therapy when combined with chemoradiotherapy. Here we consider the rationale for combining new agents with chemoradiotherapy and the evidence from clinical studies assessing multimodal strategies for the management of patients with unresectable stage III NSCLC. - Tweetable abstract ERSpublications - click to tweetThe rationale for combining new agents with chemoradiotherapy to treat stage III NSCLC and data from clinical studies http://ow.ly/nuE1d
Gesehen am 02.11.2021